Pelaksanaan Evaluasi Formatif Mata Pelajaran Ekonomi Pada Kelas Xi Di Madrasah Aliyah Al–Badar Kasongan - Supardi Supardi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
This study aims to determine the Formative Evaluation of the Implementation of Economic Subjects in class XI in Aliyah Al-Badar Lessons Kasongan academic years 2013-2014. To get the data the researchers used several methods, namely: Interview, observation, and documentation. Planning is the preparation done by teachers in economics before carrying out the formative evaluation, namely to create a syllabus and lesson plans, so that the implementation of formative evaluation can be run properly. Implementation of formative evaluation of economic subjects held in Aliyah Al - Badar is in conformity with the relevant teacher planning, even in the learning system that is taught to students of economic subjects has been going well despite the shortcomings, especially infrastructure and facilities such as libraries, laboratories, and textbooks are very minimal. Follow up of the results of the formative evaluation, after carrying out the formative evaluation of the test results will be notified to the learning outcomes of students who either can continue to the next lesson, but for the students who have not reached the learning outcomes, KKM will be held remedial for improved results. Constraints in the learning process faced by teachers are mastery of the material, therefore the teachers of economics should be ready in the mastery of the material that will be presented to the learner.